Islamic Identity And Its Characteristics: Semantic Study Of Arab Islamic Literary Works - Odeh, Ibrahim Yousef Hammad; Bin Yusoh, Fauzi; Al-Thulaia, Hussein Ali Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study comprehensively explores Islamic identity's essence and distinctive features in Arabic literature. Using a qualitative approach, the study focuses on the historical evolution, conceptual understanding, religious foundations, Islamic dimensions, and Islamic identity characteristics. The study synthesizes data from primary, secondary, and Islamic scholarly literature, providing a nuanced understanding of Islamic identity in both the Western and Eastern worlds. The research methodology includes a systematic review of relevant literature from Islamic scholars. The study emphasizes the importance of Islamic identity in uniting Muslims worldwide. It portrays Islamic identity as a concept that can help promote nationalism, ensure progress, and achieve growth in all aspects of life. The study further examines the salient characteristics of Islamic identity, attributing its unique significance in fostering multi-ideological differences, fostering unity, and transforming the perspectives of non-believers about Islam. Arabic is considered one of the most important characteristics of Islamic identity, as it is used in the Qur'an and Hadith. Classical Arabic is the crucible of Islam, the repository of its culture, and the source of most of its writings over the centuries. Learning Arabic does not mean the disappearance of local languages, but rather their strengthening and development. The Islamic Caliphate used Arabic, and these languages are not extinct. The findings of this study suggest a deeper understanding and appreciation of Islamic identity within contemporary societies, ideologies, cultural differences, and variations in religious teachings.